2007 Annual report. IICA's contribution to agriculture and the development of the rural communities in Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This 2007 annual report documents the first year of implementation of the medium-term plan, focused on four main objectives; successful organization of events and seminars beneficial to agriculture and rural life in Jamaica; promotion of agribusiness and trade; strengthen agricultural health and food security systems; and the strengthening of rural communities. This was done through several projects, the Office also moved to modernize internally, reorganizing the information center and relaunching our website. Another great success was the award of the IICA Inter-American Agricultural Medal to a Jamaican, Mr. Egbert Miller, from Circle B Farm in St. Ann.